KOTA TAMADDUN: BANTEN LAMA DALAM PERSPEKTIF ARKEOLOGI-SEJARAH ABAD 16 - Rikza Fauzan; Ana Nurhasanah; Eko Ribawati (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2023)
This study provides an overview of the formation of the city of Banten (Surosowan) in a historical-archaeological view as the center of the capital of the Sultanate of Banten with a Cosmopolitan style. This characteristic is a sign that Banten City at that time was an area that had a diverse and multicultural community structure but was very thick with Islamic entities. As the largest trading port after the fall of Malacca to the Portuguese, Banten was also the largest city of Islamic civilization (Tamaddun) on the island of Java in the sixteenth century. This can be seen from the building structure and layout of the city of Banten which has the characteristics of an Islamic civilization city. The method used in this study is the historical method which includes the heuristic, criticism, interpretation, and historiography stages. Data collection techniques with literature study of relevant sources. The historical and archaeological facts found show that there are remains that form the basis of the argument that Banten has the characteristics of being a city of Islamic civilization (Tamaddun). The focus in this study is on archaeological remains in the form of city layouts, elements of Islamic cities and the classification of buildings around the center of the old Banten city in the early period of their formation. This is also a historical description of the architectural development of Banten City around the XVI century.